2017
DOI: 10.1111/vop.12465
|View full text |Cite
|
Sign up to set email alerts
|

Biofilms of Candida spp. from the ocular conjunctiva of horses with reduced azole susceptibility: a complicating factor for the treatment of keratomycosis?

Abstract: The results demonstrate that Candida from the ocular conjunctiva of horses can pose as a risk to animal health as they are capable of forming biofilms, which are commonly involved in fungal keratitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 38 publications
1
12
0
1
Order By: Relevance
“…In addition, our results showed that 11.4% and 8.6% of C. albicans isolates were resistant to FLC and ITC, respectively. These findings are consistent with those of previous studies conducted in Portugal and China 23,24 .…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…In addition, our results showed that 11.4% and 8.6% of C. albicans isolates were resistant to FLC and ITC, respectively. These findings are consistent with those of previous studies conducted in Portugal and China 23,24 .…”
Section: Discussionsupporting
confidence: 94%
“…In this study, C. albicans isolates with the highest biofilm-forming ability among the ones tested were selected and analyzed through scanning electron microscopy (SEM), according to a previously described method 23 . After incubation and removal of free cells by washing, biofilms and sticky cells were fixed with glutaraldehyde and incubated at 4°C overnight.…”
Section: Scanning Electron Microscopic (Sem) Study Of Candida Biofilmsmentioning
confidence: 99%
“…The OD values were recorded for all tested isolates and negative controls. The isolates were then classified as non-biofilm producers when OD 590 nm ≤ ODc, weak biofilm producers, when ODc < OD 590 nm ≤ 2×ODc, moderate biofilm producers, when 2×ODc< OD 590 nm ≤ 4×ODc, and strong biofilm producers when OD 590 nm >4× ODc (Brilhante et al, 2017).…”
Section: Screening For Biofilm Formationmentioning
confidence: 99%
“…9). Hefen hingegen können häufig an ihrer Sprossung erkannt werden, hierbei zweigen von einer rundlichen Mutterzelle kleinere, ebenfalls rundliche Sprosszellen ab [14]. Bereits wenige Pilzhyphen in der Hornhautzytologie sind beweisend für eine Keratomykose [13], allerdings schließt der fehlende Nachweis das Vorliegen einer Keratomykose nicht aus.…”
Section: Probenentnahmeunclassified